From Modern Planetary Health to Decolonial Promotion of One Health of Peripheries - Baquero, Oswaldo Santos; Benavidez Fernández, Mario Nestor; Acero Aguilar, Myriam (Frontiers in Public Health, 2021)
The concept of Planetary Health has recently emerged in the global North as a concern with the global effects of degraded natural systems on human health. It calls for urgent and transformative actions. However, the problem and the call to solve it are far from new. Planetary health is a colonial approach that disregards alternative knowledge that over millennia have accumulated experiences of sustainable and holistic lifestyles. It reinforces the monolog of modernity without realizing that threats to “planetary health” reside precisely in its very approach. It insists on imposing its recipes on political, epistemological, and ontological peripheries created and maintained through coloniality. The Latin American decolonial turn has a long tradition in what could be called a “transformative action,” going beyond political and economic crises to face a more fundamental crisis of civilization. It deconstructs, with other decolonial movements, the fallacy of a dual world in which the global North produces epistemologies, while the rest only benefit from and apply those epistemologies. One Health of Peripheries is a field of praxis in which the health of multispecies collectives and the environment they comprise is experienced, understood, and transformed within symbolic and geographic peripheries, ensuing from marginalizing apparatuses. In the present article, we show how the decolonial promotion of One Health of Peripheries contributes to think and advance decentralized and plural practices to attend to glocal realities. We propose seven actions for such promotion.